Acquisition strategy factors related to faster defense acquisitions. Issue 2 (10th November 2021) - Etemadi, Amir; Kamp, John
Abstract: The Department of Defense is experimenting with rapid acquisition strategies intended to deliver new capabilities in 2–5 years. There are few historical examples of programs achieving such cycle times – the duration from program start to initial operational capability within such short durations. This paper summarizes recent research between strategy decisions during program development and eventual program durations. Regression models are developed providing initial estimates of program schedule durations and growth from a few planning decisions. Program offices may use similar models and relationships as part of setting realistic program schedule expectations.